THE RELATIONSHIP BETWEEN READING SPEED AND READING COMPREHENSION IN INDONESIAN SUBJECTS IN V GRADE ELEMENTARY SCHOOL - Siti Badriyah; Rina Yuliana (Universitas Sebelas Maret, 2018)
This study aims to determine relationship of reading to understanding readings in indonesian class v academic year 2017/2018. The method used in this research is quantitative descriptive method with correlational technique and sampling is done by random sampling technique. Technique of data collection is done through observation sheet and oral test about reading comprehension comprehension. Based on the data analysis obtained correlation coefficient in this study is 0,129 and included into very low category. The number indicates that the correlation is positive. Meanwhile, the coefficient of determination obtained is 1.6641%. These results indicate that the magnitude of the contribution of students' reading speed to the reading comprehension of students is 1.6641%. Result of correlation significance test at significant level α = 0,05 obtained tcount = 0,596 and ttable = 1,721. So it can be concluded that there is a positive relationship between the speed of reading to understanding reading but not significant.